Legal Ambiguity in Handling Cryptocurrency Evidence: Challenges and Solutions - Kartono Kartono; Neva Sari Susanti; Samuel Soewita; Agus Salim; Ali Imron (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study explores the legal ambiguities and challenges in handling cryptocurrency evidence in criminal cases, particularly in Indonesia. Cryptocurrencies, with their decentralized and anonymous nature, are increasingly being used in illegal activities such as money laundering, fraud, and drug trafficking. The absence of clear regulations on the legal status and treatment of cryptocurrencies as evidence creates significant hurdles for law enforcement, including difficulties in seizure, identification of owners, and admissibility in court. By employing a qualitative approach with descriptive analysis, the study analyzed legal frameworks, conducted interviews with legal experts, and reviewed cases involving cryptocurrencies. Findings highlight the need for clear regulations defining the legal status of cryptocurrencies, structured training programs for law enforcement on blockchain technology, and international cooperation to address cross-border challenges. The study offers actionable recommendations, including legal reform, capacity building, and enhanced international collaboration, aiming to improve governance and ensure justice in cases involving cryptocurrency evidence.